Effectiveness of Diabetes Mellitus Management Training On Health Cadres - Tavip Dwi Wahyuni; Jupriyono Jupriyono; Moh. Zainol Rachman (STAI Miftahul Ula Nganjuk, 2024)
The highest prevalence of diabetes mellitus (DM) based on diagnosis and symptoms is observed in the 55-64 year age group, at 5.5%. Knowledge about DM is crucial for sufferers to minimize the risk of complications. This study aims to analyze the effectiveness of DM management training in preventing DM complications in Kalipare Village, Malang Regency. A Quasi-Experimental design was employed in this research conducted in Kalipare Village, Malang Regency. The study population consisted of all Health Cadres in Kalipare Village, totaling 30 individuals. The research sample comprised 30 Health Cadres, selected using Total Sampling technique. The independent variable was DM management training, while the dependent variable was the prevention of DM complications. Data were collected using questionnaires and skills observation, and analyzed using the Mann-Whitney test. The results indicated a significant difference with a p-value of 0.000 (< 0.05) between the treatment group and the control group in terms of knowledge and observation of DM management skills post-treatment. This signifies the effectiveness of DM management training in preventing DM complications. The more effective the DM management training provided to health cadre participants, the better the prevention of DM complications.